2022
DOI: 10.3390/diagnostics12051240
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Monosodium Urate (MSU) Deposits in Cadavers Detected by Dual-Energy Computed Tomography (DECT)

Abstract: Background: Dual-energy computed tomography (DECT) allows direct visualization of monosodium urate (MSU) deposits in joints and soft tissues. Purpose: To describe the distribution of MSU deposits in cadavers using DECT in the head, body trunk, and feet. Materials and Methods: A total of 49 cadavers (41 embalmed and 8 fresh cadavers; 20 male, 29 female; mean age, 79.5 years; SD ± 11.3; range 52–95) of unknown clinical history underwent DECT to assess MSU deposits in the head, body trunk, and feet. Lens, thoraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Tendon involvement in patients with gout has been evaluated by US and DECT [30][31][32] and it has been shown that tendons are a frequent location of extraarticular MSU deposition in the lower limbs, especially in longstanding gout. DECT demonstrated high sensitivity, specificity, and reproducibility in the detection of MSU deposits in tendons in previous studies [26,31,33,34]. Yuan et al [3] reported tendons as the most frequent anatomical location site of MSU deposits in a DECT study of 184 joints, regardless of whether the intraarticular DECT results were positive or negative.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Tendon involvement in patients with gout has been evaluated by US and DECT [30][31][32] and it has been shown that tendons are a frequent location of extraarticular MSU deposition in the lower limbs, especially in longstanding gout. DECT demonstrated high sensitivity, specificity, and reproducibility in the detection of MSU deposits in tendons in previous studies [26,31,33,34]. Yuan et al [3] reported tendons as the most frequent anatomical location site of MSU deposits in a DECT study of 184 joints, regardless of whether the intraarticular DECT results were positive or negative.…”
Section: Discussionmentioning
confidence: 94%
“…Several typical artifacts have been well described in the literature, e.g., finger nails, tendons and vessels [ 25 ]. Only a few studies correlated DECT findings with polarizing light microscopy [ 26 ]. Given the lack of verification by microscopy of extraarticular MSU deposits in published studies, it remains questionable whether these findings represent true urate or artifact.…”
Section: Introductionmentioning
confidence: 99%
“…However, another cadaveric DECT study published by the same group of investigators found no evidence of coronary MSU deposition, although they were identified in the lens, thoracic aorta, and foot tendons. 9 In another study of 96 patients with gout and hyperuricemia and controls, 102 plaques with DECT findings suggestive of MSU deposition using default settings were reported, with 74.2% of them having evidence of calcification adjacent to the DECT MSU findings. 18 Based on the fact that beam hardening was a highly prevalent source of artifactual DECT findings in our study, further investigation of these plaques with advanced DECT measurements may have shed more clarity on whether these areas of green colorization were, in fact, suggestive of MSU deposition or artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Several published reports have shown evidence of microscopic MSU crystals in postmortem and surgical specimens. [6][7][8][9] Consequently, there has been surging interest in the novel application of dual-energy computed tomography (DECT) technology to noninvasively identify macroscopic cardiovascular MSU crystals. DECT, which has revolutionized musculoskeletal imaging in patients with gout, is a unique imaging modality that allows for the identification and quantification of MSU crystal deposits based on their chemical composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation